The Effect of Think Pair Share (TPS) Model on Students Mathematic Learning Outcomes - Abd Karim (Universitas Islam Jember, 2017)
The purpose of the research to determine whether there is effect of Think Pair Share (TPS) learning model on student learning outcomes. The kind of the research is associative with quantitative approach. The subjects of the research are students of class VII at MTs Sunan Kalijaga Banyuanyar. With the data collecting method that used is documentation, and test. The data analysis method that used is quantitative with the name of formula is chi squared. The result of the research there is influence of Think Pair Share (TPS) learning model to the students' mathematics learning outcomes.Keywords: TPS, students' mathematics learning outcomes